A community of practice approach to bioanalysis delivery: the role of the Preclinical Bioanalysis and Toxicokinetics department at AstraZeneca. (May 2014) - Wilson, Amanda; Silvester, Stephen; Woods, Karen
Retaining regulated bioanalysis within AstraZeneca (AZ) is important for the effective delivery of nonclinical and clinical bioanalysis. The focus for the in-house team is the delivery of high-throughput bioanalysis and toxicokinetics support for investigational toxicology; however, by retaining GLP compliance, AZ will have an in-house understanding of every candidate drug that is progressed into development by supporting the first rodent GLP study for each project. The majority of nonclinical bioanalysis and all of the clinical bioanalysis are delivered by two external partnership models. This article describes the key benefits of retaining GLP compliance, the partnership interactions, discusses the management of non-GLP support in a GLP environment and how, having practical experience of regulatory facing method development, validation and study execution adds value to the AZ portfolio delivery.